2022
DOI: 10.3390/coatings12081088
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-like Carbon Coatings in the Biomedical Field: Properties, Applications and Future Development

Abstract: Repairment and replacement of organs and tissues are part of the history of struggle against human diseases, in addition to the research and development (R&D) of drugs. Acquisition and processing of specific substances and physiological signals are very important to understand the effects of pathology and treatment. These depend on the available biomedical materials. The family of diamond-like carbon coatings (DLCs) has been extensively applied in many industrial fields. DLCs have also been demonstrated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Deposition of good quality DLC is governed by energy per unit carbon atom or ion and plasma kinetics, which are independent parameters. In many cases, the performance of biomedical devices can be effectively enhanced by coating them with DLCs, such as vascular stents, prosthetic heart valves and surgical instruments [4]. By drawing the running conditions fretting map and analysing the tangential stiffness, friction coefficient and dissipation energy: with increasing the sp 2 /sp 3 hybrid carbon content of DLC film, the fretting regime moves towards the slip regime, while the friction coefficient and dissipated energy will increase [5].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of good quality DLC is governed by energy per unit carbon atom or ion and plasma kinetics, which are independent parameters. In many cases, the performance of biomedical devices can be effectively enhanced by coating them with DLCs, such as vascular stents, prosthetic heart valves and surgical instruments [4]. By drawing the running conditions fretting map and analysing the tangential stiffness, friction coefficient and dissipation energy: with increasing the sp 2 /sp 3 hybrid carbon content of DLC film, the fretting regime moves towards the slip regime, while the friction coefficient and dissipated energy will increase [5].…”
Section: Introductionmentioning
confidence: 99%
“…DLC coatings have been applied in industrial fields and demonstrated to be biocompatible [1]. Its properties are optimized to identify the best parameters [2].…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with the ability to deposit conformal coatings on various substrates, enables the fabrication of compact and portable IR sensors with reduced form factors and known protection and thermal management benefits [8]. This makes hydrogenated carbon thin films ideal for emerging applications such as wearable electronics, unmanned aerial vehicles (UAVs), and Internet of Things (IoT) devices [9][10][11].…”
Section: Introductionmentioning
confidence: 99%